Kepemimpinan Etis: Rahasia Menurunkan Stres Kerja dan Turnover Intention - Bonar Bangun Jeppri Napitupulu; Gusti Nyoman Budiadnyana; Muhammad Johan; Admiral Admiral; Dewiana Novitasari (Jurnal Manajemen dan Kewirausahaan, 2021)
This study aims to examine the effect of ethical leadership on turnover intention and to investigate the mediating effect of job stress on the employee of a garment industry in Indonesia. Data was collected from 184 returned questionnaires of samples taken by random sampling. The data were analysed using an SEM method with SmartPLS 3.0 software. The results of this study show that ethical leadership has a negative significant effect of job stress and employee turnover intention, job stress has a positive significant effect on turnover intention. This new research proposed a model for managing job stress and turnover intention among the employee of the garment industry in Indonesia through developing ethical leadership practice. This research could pave the way to improve employee readiness in facing the era of industrial revolution 4.0.